Membangun Karakter Melalui Ekstrakurikuler Drum Band Di SD Negeri 1 Legian - Gita Safitri, Ni Luh; Mariana, I Made Alit; Kusuma, I Made Wirahadi (Jayapangus Press, 2021)
Drum band is one of the extracurricular activities carried out at SD Negeri 1 Legian. The activity was carried out on Tuesday at the school yard. This extracurricular activity is able to build and grow certain characters in the students who participate in it. According to the Ministry of National Education and Culture, there are 18 values ​​developed in human, religious, namely honesty, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love for the country, respect for achievement, friendship. communicative, peace-loving, fond of reading, caring for the environment, and responsibility. Researchers will associate these 18 characters with the characters that can be raised from the drum band extracurricular at SD Negeri 1 Legian. This research use constructivism theory, behaviorism theory, and value theory. This type of research data consists of primary data and secondary data obtained from observation techniques, interviews, literature study, and documentation. The results showed the following: (1) The types of activities carried out in the drum band extracurricular at SD Negeri 1 Legian, namely, praying, arriving early, playing musical instruments, cleaning musical instruments, playing different musical instruments, practicing during the day, singing the national anthem, maintaining cleanliness at the practice site, reminding, and allowing students to worship during extracurricular activities, (2) The process of implementing drum band extracurricular activities at SD Negeri 1 Legian requires students to understand 4 main parts of the drum band extracurricular, namely, percussion, brass, color guard, and majororet, (3) The values ​​contained in the drum band extracurricular at SD Negeri 1 Legian are curiosity, responsibility, discipline, religious, independent, friendly / communicative, hard work, a spirit of tolerance, and care for the environment. Each of these values ​​if applied seriously will foster human character who has good morals and ethics.